Factors Associated with Knowledge Regarding Uterine Prolapse among Women Attending Gynecology Outpatient Department of Tertiary Care Teaching Hospital (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Associated factors; Gynecology; Knowledge; Tertiary care teaching hospital; Uterine prolapse; Women